Effectiveness of Using Scramble and Expository in Improving Reading Comprehension Ability - Nisa', Qonita Izzatun; AR, Muhammad Misbahudholam; Kuswandi, Iwan (Vidya Karya, 2024)
This study aimed to determine the effect of the scramble method on reading comprehension skills in terms of the reading interest of elementary school students. The study was conducted at SDN Karangduak 1 Sumenep with 30 class IVA students as an experimental class and class IV B with a sample of 30 students as a control class. The study used treatment by level 2 x 2. The data analysis technique was a two-way analysis of variance (ANOVA). Based on the data analysis, the average results of the control class's final test (post-test) are 60.26. The average final test (post-test) of the experimental class is 71.41, which gives a t count of 3.919 and a t table (α = 5%) of 1.997, which means t count > t table (3.919 > 1.997), then Ha is accepted. From the results of the effect size (ES) calculation, an obtained ES of 0.851 with the criteria classified as high in the ES range > 0.8. This means that the use of the cooperative learning model Scramble method has a high influence on the learning outcomes of Elementary School Karangduak 1 Sumenep students.